Comparative sampling methodologies for detecting and quantifying 2,4,6 trinitrotoluene post-blast traces in water - Webb, Sally; Sharma, Bhumika; Temple, Tracey; Coulon, Frederic (Cranfield University Defence and Security, 2024)
This study addresses the analytical challenges associated with recovering explosive residues, focusing on the identification of 2,4,6-trinitrotoluene (TNT) in water samples. It evaluates the practicality, efficiency, and representativeness of three sampling methodologies: traditional grab sampling (GS), composite sampling (CS), and 3-D multi-increment sampling (3D-MIS). High-Performance Liquid Chromatography (HPLC) was employed for explosive identification. Post-blast sampling of TNT residues from high-order and low-order deflagrations was conducted to assess each method's efficacy and limitations in detecting trace and bulk contaminations. The experiments were conducted at the Alford Technologies Group range in Broadmead, UK, with analysis performed at the Defence Academy in Shrivenham, UK. Key findings highlight the varying effectiveness of each sampling method, with implications for enhancing detection sensitivity and accuracy in post-blast scenarios. This study underscores the importance of selecting appropriate sampling strategies tailored to different contamination scenarios, thereby informing more effective response protocols in CBRNE incidents involving water environments.
This work is a preliminary study to provide an overview of grab, composite and multi-increment sampling.
Keywords: sampling methods; explosives; comparative sampling